Pengaruh Religiusitas dan Pendapatan terhadap Kepatuhan Membayar Zakat Hasil Tambak - Rifqah Mursidah; Sirajuddin Sirajuddin; Akramunnas Akramunnas (Prodi Perbankan Syariah FAI UMT, 2022)
The collection of zakat malls in Indonesia is growing every year. However, the collection rate is still low. One type of zakat mal is zakat from ponds. Pond cultivation until now is counted as a business that provides extraordinary income. The revenue generated by the product encourages the community to develop the business. This study aims to determine the effect of religiosity and income on compliance with paying zakat from ponds. This study uses a survey method with a quantitative research approach. The population in this study were pond farmers in Ma'rang District, Pangkep Regency. Determination of the sample using non-probability sampling method with purposive sampling type. The criteria that have been set by the author in this case the respondents are pond farmers who are Muslim, have been farming for at least 3 years and are obliged to pay zakat. The sample used in this study was 100 respondents. The data analysis used was multiple linear regression analysis using the IBM Statistics SPSS version 26 application. The results showed that religiosity had an effect on compliance with paying zakat from ponds. Income has an effect on compliance with paying zakat from ponds.